Numerical size estimates of inclusions in Kirchhoff–Love elastic plates. (15th August 2019) - Bilotta, Antonio; Morassi, Antonino; Rosset, Edi; Turco, Emilio; Vessella, Sergio
Abstract: The size estimates approach for Kirchhoff–Love elastic plates allows to determine upper and lower bounds of the area of an unknown elastic inclusion by measuring the work developed by applying a couple field on the boundary of the plate. Although the analytical process by which such bounds are determined is of constructive type, it leads to rather pessimistic evaluations. In this paper we show by numerical simulations how to obtain such bounds for practical applications of the method. The computations are developed for a square plate under various boundary loads and for inclusions of different position, shape and stiffness. The sensitivity of the results with respect to the relevant parameters is also analyzed.